The perceived landscape in the pulsar of the Sacaí Environmental Complex, Baixo rio Branco, Roraima, Brazil - Alves, Thiago José Costa; Noda, Sandra do Nascimento; Souza, Juliane Marques de (Sustainability in Debate, 2018)
Amazonic agroecosystems are part of a complex structure, the Amazon forest. They are composed by space-time structures that are related to the vivified environment and to the farmers’ immaterial knowledge. This study aims to understand the conservation movement of autopoiesis of life in the Sacaí Environmental Complex, Caracaraí, Roraima. Brazil, from the antithetic process of space-time design of water pulse, exposed from the drought and flood landscapes. This movement brings temporality and spatiality which can be revealed through the variety of perceptions about landscape unit. Even though they are easily observable, these landscapes unities can only be accessed by the immaterial way as a result of the vivified. To achieve this, semi-structured interviews, natural resources map and REVV (Spontaneous validation meetings) were undertaken.